PENGARUH HEALING TERHADAP KONDISI MENTAL GENERASI Z DI KOTA SERANG: Indonesia - Rifal Saefudin; Isak Iskandar (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the influence of healing activities on the mental condition of Generation Z in Serang City. Generation Z is known as a group highly vulnerable to mental pressure due to academic demands, social interactions, and digital media exposure. The research method used is quantitative with an associative approach. Data were collected through a Likert-scale questionnaire and analyzed to determine the relationship between the intensity of healing activities and respondents' mental stability. The findings reveal that healing activities have a positive and significant effect on Generation Z's mental condition. Routine healing practices, such as nature tourism, quality time, self-care, and engaging with entertaining social media content, have been shown to relieve stress and enhance emotional balance. This research is expected to serve as a basis for developing mental well-being programs for youth and young adults in Serang City.